Determinants of the Adoption of Sustainable Land Management Practices and Their Impacts in the Ethiopian Highlands - World Bank (Washington, DC, 2012)
An extensive review of literature on the determinants of adoption and impacts of land management technologies in the Ethiopian highlands was undertaken to guide policy makers and development agencies in crafting programs and policies that can better and more effectively address land degradation in Ethiopia. Several generalizations emerge from the review: 1) the profitability of land management technologies is a very important factor influencing technology adoption. In many cases it is a threshold consideration; 2) land tenure insecurity and limited transfer rights undermine land management investments; 3) the impacts of household endowments on technology adoption are mixed; and 4) the impacts of credit on input use are positive where input use is profitable and not too risky; in other cases credit is not a binding constraint, because farmers ration their use of credit to avoid risk. Further research on the adoption and impacts of land management practices is needed to build on this understanding of what works, and where. Based on this review, as well as the findings from two companion papers and stakeholder workshops, it appears that research in different biophysical and socioeconomic domains to assess the off-site as well as on-site costs and benefits of alternative land management approaches will be particularly useful in supporting efforts to scale up successful sustainable land management practices in Ethiopia.